Impact of Minimum Wage on Employment and Exports in Readymade Garments in Bangladesh - Islam Liton, Muhammad Rabiul; Akhter, Roksana; Hasan, Sabiha Binta (IJRDO - Journal of Social Science and Humanities Research, 2017)
Readymade Garment (RMG) sector is the key sector of Bangladesh economy. It provides job opportunities for more than 4 million people and most of whose are women. Since last three decades, the RMG sector has become the leading export earning sector. It becomes possible only for cheap labour force. But inflation rate in Bangladesh is also high. Thus the real wage in RMG sector is very low. As a result workers lead a measureable life. So, the government announced the fifth minimum wage. Theoretically, an increase in wage may decrease employment level and create job-less situation for workers. But this study does not find any effect of increasing minimum wage in RMG sector in Bangladesh on employment level and it does not create any unemployment. So, it seems to be blessing for the workers.